Role of Innate Immune Response of Dental Hyperplastic Pulpitis: A Review - Ade Rizki Putri Ratih; Desi Oktariana (Sriwijaya Journal of Medicine, 2024)
Immunity plays an important role in many areas, including dental health. Dental caries is the main and most common problem in dental and oral health fields. Dental caries was influenced by 4 important factors, among them was a bacterial infection. The bacterial infection can cause inflammation of the pulp. Chronic inflammation pulpitis can stimulate pulp polyps or hyperplastic pulpitis. This study aimed to identify the role of innate immune response to hyperplastic pulpitis process. Bacteria Streptococcus mutans was the most prevalent bacteria in dental caries. Its lipopolysaccharide could trigger an immune response by activating the cellular and humoral components in the pulp cavity. The cellular components include polymorphonuclear cells, monocyte and macrophage cells, dendritic cells, basophil cells, and mast cells. The humoral component was histamine and pro-inflammatory cytokines, such as IL-1β, IL-4, IL-6, and IL-12. The presence of bacterial infections or pathogens causes the body to stimulate defense mechanisms through innate immune cells and humoral components.